Measurement-Based Domain Parameter Optimization in Electrical Impedance Tomography Imaging - Dusek, Jan; Mikulka, Jan (Sensors (Basel, Switzerland), 2021)
This paper discusses the optimization of domain parameters in electrical impedance tomography-based imaging. Precise image reconstruction requires accurate, well-correlated physical and numerical finite element method (FEM) models; thus, we employed the Nelder-Mead algorithm and a complete electrode model to evaluate the individual parameters, including the initial conductivity, electrode misplacement, and shape deformation. The optimization process was designed to calculate the parameters of the numerical model before the image reconstruction. The models were verified via simulation and experimental measurement with single source current patterns. The impact of the optimization on the above parameters was reflected in the applied image reconstruction process, where the conductivity error dropped by 6.16% and 11.58% in adjacent and opposite driving, respectively. In the shape deformation, the inhomogeneity area ratio increased by 11.0% and 48.9%; the imprecise placement of the 6th electrode was successfully optimized with adjacent driving; the conductivity error dropped by 12.69%; and the inhomogeneity localization exhibited a rise of 66.7%. The opposite driving option produces undesired duality resulting from the measurement pattern. The designed optimization process proved to be suitable for correlating the numerical and the physical models, and it also enabled us to eliminate imaging uncertainties and artifacts.
Keywords: elektrická impedance; complete electrode model; počítačové zpracování obrazu; Phantoms, Imaging; domain deformation; electrical impedance tomography; tomografie; electrode locations; algoritmy; Computer Simulation; počítačová simulace; Algorithms; Tomography; Electric Impedance; fantomy radiodiagnostické; Image Processing, Computer-Assisted; Nelder–Mead optimization